Técnicas de geoprocessamento e dados neotectônicos para identificação de áreas favoráveis à captação de água subterrânea (porção centro/norte do Estado do Espírito Santo, sudeste do Brasil) - Santos, Talles Gomes (2019)
This research had the main objective a mapping of hydrogeological favorability in the north-central portion of the state of Espírito Santo, using products generated by geoprocessing and neotectonic techniques. The methodological basis used integrated cabinet analysis and field data available in the literature. In the cabinet were performed: i) literature review; ii) manual extraction of lineaments on the scale; iii) Linearity density; iv) fracture rate; v) slope map vi) rainfall map vii); drilling wells and viii) analysis of neotectonic data in the literature. Based on the elaborated products and data integration, it shows that the studied area has a high underground water potential, especially in the Pre-Cambrian Basement Compartment. . Areas that represent high water potential correspond to areas located in the northwest and central portions of the studied area in the geological compartment of the Pre cambrian Basement and south of the studied area, along the Doce River in the geological Cenozoic Deposits Compartment and those areas with low water potential were the southeast, north and northeast areas of the study area in the Cenozoic Depot compartment. Faults, fracture and high fracture rates were essential to point out groundwater storage sites along with geoprocessing techniques used in this work as important tools to point out the areas with high water potential.